Visualization of both proximal M2-MCA segments in patients (the Tilted-V Sign) with acute M1-MCA occlusion stroke is associated with better procedural and prognostic outcomes - Amit Azriel; Anat Horev; Elad Avraham; Farouq Alguayn; Yair Zlotnik; Gal Ifergane; Yuval Zeev Sufaro; Yotam Dizitzer; Israel Melamed; Ilan Shelef; José E. Cohen; Ronen R. Leker; et al. (Frontiers in Neurology, 2022)
IntroductionWe aimed to assess the clinical significance of M1-MCA occlusion with visualization of both MCA-M2 segments [“Tilted-V sign” (TVS)] on initial CT angiography (CTA) in patients with acute ischemic stroke (AIS) undergoing endovascular thrombectomy (EVT).MethodsData for patients with consecutive AIS undergoing EVT for large vessel occlusion (LVO) in two academic centers are recorded in ongoing databases. Patients who underwent EVT for M1-MCA occlusions ≤ 6 h from symptom onset were included in this retrospective analysis.ResultsA total of 346 patients met the inclusion criteria; 189 (55%) had positive TVS. Patients with positive TVS were younger (68 ± 14 vs. 71 ± 14 years, P = 0.028), with similar rates of vascular risk factors and baseline modified Rankin scores (mRS) 0–2. The rates of achieving thrombolysis in cerebral ischemia (TICI) 2b-3 were similar to the two groups (79%), although successful first-pass recanalization was more common with TVS (64 vs. 36%, p = 0.01). On multivariate analysis, higher collateral score [odds ratio (OR) 1.38 per unit increase, p = 0.008] and lower age (OR 0.98 per year increase, p = 0.046) were significant predictors of TVS. Patients with positive TVS had higher post-procedural Alberta Stroke Program Early CT Score (ASPECTS; 6.9 ± 2.2 vs. 5.2 ± 2.3, p = 0.001), were discharged with lower National Institutes of Health Stroke Score (NIHSS; 6±6 vs. 9±7, p = 0.003) and higher rates of mRS 0–2 (29.5 vs. 12%, p = 0.001), and had lower rates of 90-day mortality (13.2 vs. 21.6%, p = 0.038). However, TVS was not an independent predictor of functional independence (OR 2.51; 95% CI 0.7–8.3).ConclusionTilted-V Sign, an easily identifiable radiological marker, is associated with fewer recanalization attempts, better functional outcomes, and reduced mortality.